Surface thermography using dual channel imaging based on the blue and red emission of Ba3MgSi2O8:Eu2+, Mn2+. (21st November 2017) - Hashemi, A; Gast, J; Ali, A; Osvet, A; Vetter, A; Stern, E; Batentschuk, M; Brabec, C J
Abstract: In this investigation, we present a surface temperature determination method based on the luminescence characteristics of Ba3 MgSi2 O8 :Eu 2+, Mn 2+ . Simple optics utilizing only one RGB scientific CMOS camera makes this measurement technique easily applicable. Four different imaging methods were developed and are presented together with the corresponding calibration curves. We successfully utilized the methods to take a surface temperature distribution image on glass plates with a point heat source between them.